Efecto de tres tratamientos pregerminativos sobre la germinación y viabilidad de las semillas de Enterolobium cyclocarpum (Jacq) Griseb - Somarriba, Eduardo; Ferreiro, O (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Non-treated seeds of Enterolobium cyclocarpum (Jacq} Griseb achieved a 9% germination 30 days after planting. Soaking the seeds in concentrated sulfuric acid and in boiling water raised germination up to 87% and 83% respectively. Immersion in cold water during 24 hours produced a germination index of 1170. Non-germinated seeds after these treatments. when treated again with boiling water achieved the same germination index as that of the former treatment.